Experimental Study on the Influence of Berms and Roughness on Wave Overtopping at Rock-Armoured Dikes - Weiqiu Chen; Alberto Marconi; Marcel R. A. van Gent; Jord J. Warmink; Suzanne J. M. H. Hulscher (Journal of Marine Science and Engineering, 2020)
The average overtopping discharge is an important parameter for the design and reinforcement of dikes. Rock armour on the waterside slopes and berms of dikes is widely used to reduce the wave overtopping discharge by introducing slope roughness and dissipation of energy in the permeable armour layer. However, methods for estimating the influence of a rock berm and roughness of rock armour at dikes on the average overtopping discharge still need to be developed and/or validated. Therefore, this study aims to develop empirical equations to quantify the reductive influence of rock armour on wave overtopping at dikes. Empirical equations for estimating the effects of rock berms and roughness are derived based on the analysis of experimental data from new physical model tests. The influence of roughness of the rock armour applied on parts of waterside slopes is estimated by introducing the location weighting coefficients. Results show that the newly derived equations to predict the average overtopping discharge at dikes lead to a significantly better performance within the tested ranges compared to existing empirical equations.